2019
DOI: 10.18203/2394-6040.ijcmph20192311
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ satisfaction regarding facilities and services provided at AYUSH clinics of primary health centres in rural Puducherry

Abstract: Background: Patient satisfaction is a crucial component of the health care system in today’s competitive modern era. There is a limited literature describing the patient satisfaction on AYUSH care and therefore this study was undertaken to assess the satisfaction about facilities, healthcare providers and treatment among the patients attending selected AYUSH-attached PHCs in rural Puducherry.Methods: A facility based cross-sectional study was conducted among the patients who attended AYUSH clinics at 4 selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Our results are consistent with previous studies conducted by Nabi et al (13) and Boovaragasamy and Narayanan (14), which have recorded high rates of satisfaction among patients visiting AYUSH hospitals. Boovaragasamy and Narayanan recorded that 71.23% of patients found their experience with the health care providers as very good or excellent and in terms of satisfaction with service facilities, the rating as very good or excellent ranged from 64.47% to 93.93% across the different AYUSH primary health centers.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous studies conducted by Nabi et al (13) and Boovaragasamy and Narayanan (14), which have recorded high rates of satisfaction among patients visiting AYUSH hospitals. Boovaragasamy and Narayanan recorded that 71.23% of patients found their experience with the health care providers as very good or excellent and in terms of satisfaction with service facilities, the rating as very good or excellent ranged from 64.47% to 93.93% across the different AYUSH primary health centers.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous studies. For example, Boovaragasamy et al reported that ≥64.5% of 584 patients were satisfied with rural healthcare and the medical infrastructure facilities in Puducherry [32]. Additionally, Mutaganzwa et al found that ≥50% of patients were satisfied with the antenatal care and maternity services in rural Rwanda [34], and 53.2% of young adult, rural Latinos were satisfied with the healthcare services they had used previously [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a better understanding of patient satisfaction with rural medical services and potential determinants would help policy- and decision-makers to implement programs better tailored to rural patients’ health needs and desires and further improve rural health systems [30,31]. Some evidence has been found about patient satisfaction with rural medical services in Italy [25], South Africa [26], India [32,33], Rwanda [34], Bangladesh [35], Latin America [36], and the U.S. [37]. In China, one of the five key objectives of China’s new healthcare reform, launched in 2009, is to strengthen the basic-level health service delivery system, especially the rural health system.…”
Section: Introductionmentioning
confidence: 99%